Social Media Marketing In Developing Lazisnu Products - Ni Gusti Ayu Arda Suari; Asriani Asriani; Nasrullah Sopyan (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
In order to address a number of issues, this study attempts to determine the most effective marketing techniques for Lazisnu items, particularly when it comes to social media marketing. Field observation techniques and a qualitative approach with a scientific foundation were used in this study to interpret the occurrences that were observed. The study's findings indicate that the internal and external variables of the research object have an impact on marketing strategy efforts. The existence of Lazisnu, the degree of rivalry among rivals, people's enthusiasm in starting their own businesses, and people's limited saving capacity are examples of external variables. Internal issue factors, on the other hand, prevent marketing strategies from being successful. These include subpar human resource quality, less creative promotional efforts, a lack of infrastructure and funding, and a failure to keep up with digitalization trends in the marketing industry.